Desafios do estado quanto à incorporaç\~ao de medicamentos no Sistema Único de Saúde - Fabiola Sulpino Vieira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– Technology management is currently a major challenge to health systems. Scientific and technological development in recent decades has made possible to offer sophisticated treatments for various diseases, contributing to the increase of the population's expectations and quality of life. However, access to these advances has not become universal. Considering this reality, the objectives of this text are to point out and discuss challenges that the State face in relation to the incorporation of drugs in the Unified Health System (SUS). It was taking into account the principles that guide the therapeutic assistance offered through the system, its current process of health technology assessment and the budgetary constraint imposed on the system, in recent years, by economic crisis and by fiscal austerity. Documents that establish the legal framework of this issue, scientific articles and information on the spending on medicines and access to these products were used to support the arguments presented in this text. Finally, we recognize the advances promoted by the SUS regarding the supply of health goods and services to the population and the technology assessment process, but also the need to improve health technology management and pharmaceutical services policies.
Keywords: I10; 330; technology assessment; pharmaceutical preparations; pharmaceutical services; access to essential medicines and health technologies; health equity